Earthquake Performance of Reinforced Concrete Frames with Different Infill Walls - Coşan, Hüsnü (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Infill walls are used frequently as interior or exterior partitions in reinforced concrete frames in the world. The behavior of infill wall frames have been studied experimentally and analytically by a number of researchers and it has been recognized that infill walls have important effects on dynamic characteristics of structural system. However, these effects of infill walls neglected in analysis of buildings. For this reason, the horizontal rigidity effect of infill walls has not been proven to be a valid model. Therefore, infill walls generally defined as dead load in the analysis to stay on the safe side but ignoring the infill panel interaction is not always on the safe side under lateral loads. It may adversely affect the structural system during an earthquake. The main purpose of this study is the effects of infill walls on the structural behavior which are not accounted in the structural design of reinforced concrete buildings. For this purpose, nonlinear analyzes were performed using dissimilar modeling methods proposed by different researchers. These methods were analyzed using different analyze softwares. Three separate building systems were used for each different method. Hence, diverse building models have been created and the behaviors of these structures under lateral loads have been investigated in order to identify the effects of infill walls. Each building model created was analyzed in three different situations including bare frame, the frame with brick infill wall and the frame with Autoclaved Aerated Concrete (AAC) infill wall. Hereby, the outcomes obtained from analysis on bare frame and the frame with infill walls has been compared. At the end of the analysis, it is observed that infill walls have significant effect on structural period, lateral displacement, base shear force and structural behavior. Keywords: Infill wall, structural period, lateral displacement, base shear force, earthquake

ÖZ : Dünyada bölme duvarlar, betonarme çerçeve sistemlerde iç ve dış elemanlar olarak sıklıkla kullanılmaktadır. Birçok araştırmacı dolgu duvarlı çerçeveler üzerinde deneysel ve analitik olarak çalışma yapmış ve dolgu duvarların yapı sisteminin dinamik özellikleri üzerinde önemli etkilere sahip olduğunu kabul etmişlerdir. Ancak dolgu duvarların bu etkileri bina analizlerinde ihmal edilmektedir. Bunun nedeni, dolgu duvarların yatay dayanıma olan etkisinin halen kanıtlanmış geçerli bir modeli olmamasıdır. Bu nedenle, analizlerde dolgu duvarlar genellikle güvenli tarafta kalabilmek için ölü yük olarak tanımlanmaktadır. Fakat dolgu paneli etkileşiminin göz ardı edilmesi yatay yükler altında her zaman güvenli değildir. Deprem esnasında yapı sistemine olumsuz etkileri olabilir. Bu çalışmanın amacı, betonarme yapı tasarımında hesaba katılmayan bölme duvarların yapı davranışı üzerindeki etkileridir. Bu amaç için farklı araştırmacıların dolgu duvarlar için önerilen farklı modelleme metotları kullanılarak analizler gerçekleştirilmiştir. Bu farklı modelleme metotlarının analizleri farklı analiz programları kullanılarak yapılmıştır. Her farklı modelleme tekniği için üç farklı bina sistemi kullanılmıştır. Farklı model yapılar oluşturulmuş ve dolgu duvarların etkisini belirlemek amacıyla bu yapıların yatay yükler altındaki davranışları incelenmiştir. Her yapı modeli boş çerçeve, tuğla dolgu duvarlı ve gazbeton dolgu duvarlı çerçeve olacak şekilde oluşturulmuş ve üç farklı durumlarda analiz edilmiştir. Böylelikle dolgu duvarlar boş çerçeve ve dolgu duvarlı çerçeve analizlerinden elde edilen sonuçlarla karşılaştırılmıştır. Analizler sonunda, dolgu duvarların periyot, yanal deplasman, taban kesme kuvveti ve yapı davranışı üzerinde önemli bir etkiye sahip olduğu gözlemlenmiştir. Anahtar kelimeler: Dolgu duvar, periyot, yanal deplasman, taban kesme kuvveti, deprem
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2014. Supervisor: Assist. Prof. Dr. Giray Özay.
Keywords: Civil Engineering; Earthquake resistant design; Earthquake resistant design - Concrete construction - Reinforced concrete; Buildings - Earthquake effects; Reinforced concrete - Reinforced concrete construction; Infill wall; structural period; lateral displacement; base shear force; earthquake